2D Materials and Heterostructures at Extreme Pressure. Issue 24 (10th November 2020) - Zhang, Linglong; Tang, Yilin; Khan, Ahmed Raza; Hasan, Md Mehedi; Wang, Ping; Yan, Han; Yildirim, Tanju; Torres, Juan Felipe; Neupane, Guru Prakash; Zhang, Yupeng; Li, Quan; Lu, Yuerui
Abstract: 2D materials possess wide‐tuning properties ranging from semiconducting and metallization to superconducting, etc., which are determined by their structure, empowering them to be appealing in optoelectronic and photovoltaic applications. Pressure is an effective and clean tool that allows modifications of the electronic structure, crystal structure, morphologies, and compositions of 2D materials through van der Waals (vdW) interaction engineering. This enables an insightful understanding of the variable vdW interaction induced structural changes, structure–property relations as well as contributes to the versatile implications of 2D materials. Here, the recent progress of high‐pressure research toward 2D materials and heterostructures, involving graphene, boron nitride, transition metal dichalcogenides, 2D perovskites, black phosphorene, MXene, and covalent–organic frameworks, using diamond anvil cell is summarized. A detailed analysis of pressurized structure, phonon dynamics, superconducting, metallization, doping together with optical property is performed. Further, the pressure‐induced optimized properties and potential applications as well as the vision of engineering the vdW interactions in heterostructures are highlighted. Finally, conclusions and outlook are presented on the way forward. Abstract : Pressure can modify the electronic structures, crystal structures, morphologies, and compositions of 2D materials, which contributes to their versatile implications. Here, the recent progress of high‐pressure research of 2D materials and associated heterostructures is summarized. The structure, phonon dynamics, superconducting, metallization, doping, optical property, optimized properties, and future research directions of them are discussed in detail.